Determinants of stock market performance: analytical study of Malaysia and Ghana stock market performance / Nur Nabihah Annuar - Annuar, Nur Nabihah (2021)
In terms of finance, economy, and savings, the performance of stock market is significantly related to the macroeconomics stability of a country. Macroeconomics variables such as Inflation rate, exchange rate, and crude palm oil production growth rate give a positive relationship towards market performance and it is stated by Fama (1981), Arshad, and Yahya (2016). In this research, Malaysian financial known as has a stable performance compared to Ghana even though Ghana has a population of 2 million lower than Malaysia. But, on the other side, stock market performance in Malaysia has decreased slightly over the last 5 years compared to Ghana. Ghana has a higher stock market composite index than Malaysia. This is because it is possible that disputes and political-related problems experienced by Malaysia cause investors are no longer interested in the stock market in Malaysia. Recently, the instability of the capital. The Malaysian Composite Index (KLCI) has received a lot of attention from researches. One of the reasons investors are not interested in the stock market in Malaysia is due to the perceived corruption in Malaysia compared to Ghana. This study will present the issue of the study, objectives, methodology, and also the interpretation of empirical results from the tests that involved all the independent variables. The writer uses the E-Views application to analyze the results in multiple linear regression. The result of this research indicates that those independent variables related to stock market performance in Malaysia and Ghana.